System resource theory approach and its application in the study of information technology investment and firm performance a conceptual paper / Amri Mohamad and Tuan Mohd Rosli Tuan Hassan - Mohamad, Amri; Tuan Hassan, Tuan Mohd Rosli (Unit Penerbitan Universiti Teknologi MARA, Kelantan, 2017)
This research was carried out mainly to find out the conceptual linkages on the relationship between IT investment and multidimensional performance measurement in electrical and electronic manufacturing setting in Malaysia. The focus on IT investment as the independent variable was made because of the huge amount allocated for it annually and the amount keeps on increasing over the years. Further to that, the issue of 'productivity paradox' which has been an ongoing debate for quite a number of years was another pulling factor of why this research was carried out. In addition to that, this research presented the study on the use of multiple measures of performance in the electrical and electronic (E&E) manufacturing firms in Malaysia. To be more specific, it examines how IT Investment which is categorized into four types according to its IT investment objective; namely infrastructure, transactional, strategic and informational, affects a firm's multidimensional performance measurement system represented by the balanced scorecard approach which has four perspectives; namely financial, internal business process, innovation and growth, and customer perspective. The objectives for this research are to establish the conceptualizations of IT investment and multidimensional performance measurement and to gauge on the extent of conceptual relationship between IT investment and manufacturing firm performance. The aims and objectives of this research were accomplished when the conceptualizations of each of the dimensions namely IT investment and multidimensional performance measures in use are established and the linkages are clearly explained.